HUBUNGAN PENGETAHUAN DAN SIKAP IBU TERHADAP PERILAKU PENCEGAHAN COVID-19 PADA ANAK BALITA - Kenia Cynthia Putri; Arvida. Bar (NHM PRESS, 2022)
Mother's behavior in preventing COVID-19 includes washing hands both with soap and hand sanitizer, maintaining distance, implementing appeals to stay at home, avoiding crowds and physical and social distancing. This study is a quantitative study with a cross-sectional design that aims to determine the relationship between mother's knowledge and attitudes with Covid-19 prevention behavior in children under five. The population in this study were all mothers who had children under five in the work area of the Simpang IV Sipin Health Center in 2021 as many as 1527 respondents. The sample in this study were mothers who have children under five in the Simpang IV Sipin Health Center Work Area in 2021 as many as 100 respondents. The sampling technique in this research is purposive sampling. The results showed that 18 (18%) mothers had poor knowledge, 34 (34%) mothers had sufficient knowledge and 48 (48%) mothers had good knowledge. A total of 34 (34%) mothers had a negative attitude, and as many as 66 (66%) mothers had a positive attitude, as many as 34 (34%) mothers had less good covid 19 prevention behavior and as many as 66 (66%) mothers had covid 19 prevention behavior. good. The results of the statistical test obtained p-value = 0.000, which means p-value <0.05, it can be concluded that there is a relationship between knowledge and attitude with Covid 19 prevention behavior in children under five The community is expected to increase knowledge and behavior to prevent disease transmission, both from print media and during visits to health centers